Value Creation through Agro-Tech Business Model Components: Evidence from a Developing Economy - Falilat Abdul; Oluwayomi Olota; Ebenezer Balogun; Opeyemi Babawale (Universitas Muhammadiyah Malang, 2025)
Agro-business productivity in developing economies remains constrained by persistent challenges, including outdated agricultural practices, limited access to financial capital, and insufficient technological integration. This study examines how value creation within an agro-tech business model influences productivity in the agro-business sector. It specifically evaluates the effects of value proposition, customer segmentation, key activities, and key resources on productivity performance. A quantitative survey design was utilized, employing a structured questionnaire administered to 162 respondents selected from a total population of 282 employees at Olam Fish Feed, a firm based in Nigeria. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that customer segmentation (p = 0.004), key activities (p = 0.000), key resources (p = 0.016), and value proposition (p = 0.001) each have a positive and statistically significant impact on agro-business productivity. The study concludes that value-driven agro-tech business models substantially improve productivity in the agro-business sector of emerging economies. It recommends that enterprise leaders prioritize the development of strategic key resources, cultivate well-defined customer segments, articulate compelling value propositions, and focus on operational activities that foster innovation and productivity.